Comparative efficacies of various corticosteroids for preventing postextubation stridor and reintubation: a systematic review and network meta-analysis - Feng, I-Jung; Lin, Jia-Wei; Lai, Chih-Cheng; Cheng, Kuo-Chen; Chen, Chin-Ming; Chao, Chien-Ming; Wang, Ying-Ting; Chiang, Shyh-Ren; Liao, Kuang-Ming (Frontiers in Medicine, 2023)
Objectives: We assessed the efficacies of various corticosteroid treatments for preventing postexubation stridor and reintubation in mechanically ventilated adults with planned extubation Methods: We searched the Pubmed, Embase, the Cochrane databases and ClinicalTrial.gov registration for articles published through September 29, 2022. Only randomized controlled trials (RCTs) that compared the clinical efficacies of systemic corticosteroids and other therapeutics for preventing postextubation stridor and reintubation were included. The primary outcome was postextubation stridor and the secondary outcome was reintubation. Results: The 11 assessed RCTs reported 4 nodes: methylprednisolone, dexamethasone, hydrocortisone, and placebo, which yielded 3 possible pairs for comparing the risks of post extubation stridor and 3 possible pairs for comparing the risks of reintubation. The risk of postextubation stridor was significantly lower in dexamethasone-and methylprednisolone-treated patients than in placebo-treated patients (dexamethasone: OR= 0.39; 95% CI = 0.22-0.70; methylprednisolone: OR = 0.22; 95% CI = 0.11-0.41). The risk of postextubation stridor was significantly lower in methylprednisolone-treated patients than in hydrocortisone-treated: OR = 0.24; 95% CI = 0.08-0.67) and dexamethasone-treated patients: OR = 0.55; 95% CI = 0.24-1.26). The risk of reintubation was significantly lower in dexamethasone-and methylprednisolone-treated patients than in placebo-treated patients:(dexamethasone: OR = 0.34; 95% CI = 0.13-0.85; methylprednisolone: OR = 0.42; 95% CI = 0.25-0.70). Cluster analysis showed that dexamethasone-and methylprednisolone-treated patients had the lowest risks of stridor and reintubation. Subgroup analyses of patients with positive cuff-leak tests showed similar results.Conclusions: Methylprednisolone and dexamethasone were the most effective agents against postextubation stridor and reintubation.